Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the solutions of the equation [tex]\( x^4 - 5x^2 - 14 = 0 \)[/tex], we can follow a systematic, step-by-step approach.
1. Substitute [tex]\( u = x^2 \)[/tex]:
This substitution reduces the quartic equation to a quadratic form. We substitute [tex]\( u = x^2 \)[/tex], transforming the equation into:
[tex]\[ u^2 - 5u - 14 = 0 \][/tex]
2. Solve the quadratic equation [tex]\( u^2 - 5u - 14 = 0 \)[/tex]:
To solve this quadratic equation, we use the quadratic formula [tex]\( u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -5 \)[/tex], and [tex]\( c = -14 \)[/tex].
First, we calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = (-5)^2 - 4(1)(-14) = 25 + 56 = 81 \][/tex]
Now, we find the roots:
[tex]\[ u_1 = \frac{5 + \sqrt{81}}{2 \cdot 1} = \frac{5 + 9}{2} = \frac{14}{2} = 7 \][/tex]
[tex]\[ u_2 = \frac{5 - \sqrt{81}}{2 \cdot 1} = \frac{5 - 9}{2} = \frac{-4}{2} = -2 \][/tex]
3. Back-substitute [tex]\( u = x^2 \)[/tex]:
We revert back to [tex]\( x \)[/tex] from [tex]\( u \)[/tex] by solving the equations [tex]\( x^2 = u_1 \)[/tex] and [tex]\( x^2 = u_2 \)[/tex].
- For [tex]\( x^2 = 7 \)[/tex]:
[tex]\[ x = \pm \sqrt{7} \][/tex]
- For [tex]\( x^2 = -2 \)[/tex]:
Since [tex]\( x \)[/tex] must be a complex number to satisfy this equation, we have:
[tex]\[ x = \pm \sqrt{-2} = \pm i \sqrt{2} \][/tex]
Thus, the solutions to the equation [tex]\( x^4 - 5x^2 - 14 = 0 \)[/tex] are:
[tex]\[ x = \pm \sqrt{7}, \pm i \sqrt{2} \][/tex]
The correct solution is:
[tex]\[ x= \pm \sqrt{7} \, \text{and} \, x= \pm i \sqrt{2} \][/tex]
1. Substitute [tex]\( u = x^2 \)[/tex]:
This substitution reduces the quartic equation to a quadratic form. We substitute [tex]\( u = x^2 \)[/tex], transforming the equation into:
[tex]\[ u^2 - 5u - 14 = 0 \][/tex]
2. Solve the quadratic equation [tex]\( u^2 - 5u - 14 = 0 \)[/tex]:
To solve this quadratic equation, we use the quadratic formula [tex]\( u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -5 \)[/tex], and [tex]\( c = -14 \)[/tex].
First, we calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = (-5)^2 - 4(1)(-14) = 25 + 56 = 81 \][/tex]
Now, we find the roots:
[tex]\[ u_1 = \frac{5 + \sqrt{81}}{2 \cdot 1} = \frac{5 + 9}{2} = \frac{14}{2} = 7 \][/tex]
[tex]\[ u_2 = \frac{5 - \sqrt{81}}{2 \cdot 1} = \frac{5 - 9}{2} = \frac{-4}{2} = -2 \][/tex]
3. Back-substitute [tex]\( u = x^2 \)[/tex]:
We revert back to [tex]\( x \)[/tex] from [tex]\( u \)[/tex] by solving the equations [tex]\( x^2 = u_1 \)[/tex] and [tex]\( x^2 = u_2 \)[/tex].
- For [tex]\( x^2 = 7 \)[/tex]:
[tex]\[ x = \pm \sqrt{7} \][/tex]
- For [tex]\( x^2 = -2 \)[/tex]:
Since [tex]\( x \)[/tex] must be a complex number to satisfy this equation, we have:
[tex]\[ x = \pm \sqrt{-2} = \pm i \sqrt{2} \][/tex]
Thus, the solutions to the equation [tex]\( x^4 - 5x^2 - 14 = 0 \)[/tex] are:
[tex]\[ x = \pm \sqrt{7}, \pm i \sqrt{2} \][/tex]
The correct solution is:
[tex]\[ x= \pm \sqrt{7} \, \text{and} \, x= \pm i \sqrt{2} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.